2011
DOI: 10.1175/2010jamc2624.1
|View full text |Cite
|
Sign up to set email alerts
|

A Synthetic Aperture Radar–Based Climatology of Open-Cell Convection over the Northeast Pacific Ocean

Abstract: This paper presents an 8-yr (1999-2006) climatology of the frequency of open-cell convection over the northeastern Pacific Ocean and the thermodynamic and kinematic environment associated with its development. The climatology is based on synthetic aperture radar-derived wind speed images and reanalysis data. The climatology shows that open-cell convection was a cold-season phenomenon, having occurred in environments in which the difference in temperature between the near-surface air and the sea surface is neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 58 publications
(73 reference statements)
3
27
0
Order By: Relevance
“…However, there is some indication that the region of maximum pressure-wind balance and buoyancy terms is skewed towards the leading edge of the cell in the parallel cross-sections, a result that is confirmed by inspection of the horizontal fields of buoyancy and pressure balance. This result mirrors the observational evidence presented by Sikora et al (2011), who used synthetic aperture-radar-derived wind-speed images and visual satellite images over the north-east Pacific Ocean to suggest that OCC often takes on an arc-shape, with the largest cumulus clouds at the leading edge of the cell and smaller cumulus clouds making up the ring of the sides and trailing edge of the cell. The link between these observational results and the modelling results presented here is an interesting area for further study.…”
Section: Discussionsupporting
confidence: 87%
“…However, there is some indication that the region of maximum pressure-wind balance and buoyancy terms is skewed towards the leading edge of the cell in the parallel cross-sections, a result that is confirmed by inspection of the horizontal fields of buoyancy and pressure balance. This result mirrors the observational evidence presented by Sikora et al (2011), who used synthetic aperture-radar-derived wind-speed images and visual satellite images over the north-east Pacific Ocean to suggest that OCC often takes on an arc-shape, with the largest cumulus clouds at the leading edge of the cell and smaller cumulus clouds making up the ring of the sides and trailing edge of the cell. The link between these observational results and the modelling results presented here is an interesting area for further study.…”
Section: Discussionsupporting
confidence: 87%
“…Numerous examples of this type of blistered backscatter pattern have been seen in SAR images of sea surface, linking them to the MCC [Atkinson and Zhang, 1996;Babin et al, 2003]. Young et al [2007] and Sikora et al [2011] have described the morphology of open cell convection using RS-1 and MODIS data; the morphology of our RS-2 SAR image signals is similar to their descriptions. The MODIS image (Figure 1e) that is closest to the SAR image time occurred at 22:10:00 UTC on 1 February; it suggests that MCC did occur and that the SAR image area appears to be a transition zone between open and closed MCC.…”
Section: Polsar Datamentioning
confidence: 59%
“…Increased wind shear provides enhanced momentum transfer to the sea surface via shear- driven surface layer turbulence. In an alternate view of things, Young et al [2007] and Sikora et al [2011] suggest that the signatures of open MCC are possibly tied to downdrafts fueled by evaporation, sublimation, or melting, which could constitute momentum mix-down in conjunction with precipitation. In any case, enhanced momentum transfer impacts the mean wind in the boundary layer and associated ocean waves.…”
Section: Imaging Atmospheric Convection In Sar Imagerymentioning
confidence: 99%
“…Of interest to the research that is presented here is the finding by Sikora et al (2011) that the vertical distribution of environmental vertical wind shear found in their climatography is conducive to the organization of convection via the shear's interaction with precipitation-driven cold pools (e.g., Johnson et al 2005). That interaction is referred to herein as cold-pool dynamics.…”
Section: Introductionmentioning
confidence: 94%
“…That interaction is referred to herein as cold-pool dynamics. The resulting organization reported by Sikora et al (2011) manifests as an arc of deeper convective clouds that correspond to a squall and trailing shallower convective clouds ringing a nearly cloud-free lull, with the opencell convection typically occurring in fields. See Figs.…”
Section: Introductionmentioning
confidence: 99%